SUSTAINABLE BUSINESS MODELS IN THE DANCE INDUSTRY: INTEGRATION OF ARTISTIC AND ECONOMIC ACTIVITIES: SUSTAINABLE BUSINESS MODELS IN THE DANCE INDUSTRY: INTEGRATION OF ARTISTIC AND ECONOMIC ACTIVITIES - Ping, Xiao; Nursilah, Nursilah; Alhempi, R. Rudi (International Journal of Performing Arts (IJPA), 2025)
The dance industry faces challenges in economic sustainability due to the increasingly complex and rapidly changing dynamics of the arts market. This study aims to design a sustainable business model that integrates artistic and economic dimensions in dance production practices. By adopting a descriptive qualitative approach and reviewing literature from various sources, this study explores performing arts monetization practices, revenue diversification strategies, and digital technology-based innovations such as crowdfunding, merchandise, and digital products. The study results show that the sustainability of the dance industry is highly dependent on the ability of artists to build an adaptive, collaborative, and culturally value-based business system. The integration of choreographers' artistic visions and economic strategies has been shown to increase the resilience of arts organizations to crises, expand their audience base, and strengthen the socio-economic legitimacy of dance. This study provides a conceptual contribution to the development of an arts business model framework relevant to the context of the creative industry in the digital era, as well as practical implications for artists and policymakers in supporting a sustainable performing arts ecosystem.